Polarization and rising wage inequality: comparing the U.S. and Germany - Dirk Antonczyk; Thomas DeLeire; Bernd Fitzenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper compares trends in wage inequality in the U.S. and Germany using an approach developed by MaCurdy and Mroz (1995) to separate age, time, and cohort effects. Between 1979 and 2004, wage inequality increased strongly in both the U.S. and Germany but there were various country specific aspects of this increase. For the U.S., we find faster wage growth since the 1990s at the top (80% quantile) and the bottom (20% quantile) compared to the median of the wage distribution, which is evidence for polarization in the U.S. labor market. In contrast, we find little evidence for wage polarization in Germany. Moreover, we see a large role played by cohort effects in Germany, while we find only small cohort effects in the U.S.. Employment trends in both countries are consistent with polarization since the 1990s. We conclude that although there is evidence in both the U.S. and Germany which is consistent with a technology-driven polarization of the labor market, the patterns of trends in wage inequality differ strongly enough that technology effects alone cannot explain the empirical findings.
Keywords: J30; J31; 330; Wage Inequality; Polarization; International Comparison; Cohort Study; Quantile Regression; Lohnstruktur; Einkommensverteilung; Kohortenanalyse; Vergleich; Schätzung; USA; Deutschland